Pengembangan Modul Pelatihan Digital untuk Meningkatkan Kemampuan Guru Dalam Membuat Media Pembelajaran Komik Digital Berbantu Pixton Dan Canva - Janty Wattimena; Yari Dwikurnaningsih; Mawardi (Attractive : Innovative Education Journal, 2025)
This research is motivated by the suboptimal competence of teachers in Cluster 3 of Jayapura Regency in creating digital learning media due to the existing training modules being too theoretical. This study aims to develop a digital training module to improve teachers' ability to create digital comic media with the help of Pixton and Canva. The research method uses the Research and Development (R&D) model of Borg and Gall modified by Sukmadinata, including preliminary studies, development, and product testing. The results of the validation by material and media experts show that the module is categorized as Valid with an average score of 3.06 and 3.25, respectively. The practicality test obtained a percentage of 91.07% with the Very Practical category. The effectiveness test showed a significant increase in learning outcomes from an average pre-test of 66.89 to a post-test of 90.44, with an N-Gain score of 0.71 (High Category). It is concluded that this training module is feasible, practical, and effective for improving teachers' abilities in developing visual-based learning media.